Perceptions of the Beach Users :A Case Study of the Coastal Areas of North Cyprus Towards Establishment of a Carrying Capacity - Alipour, Habib; Altınay, Mehmet; Hussain, Kashif; Sheikhani, Nazita (Tourism Analysis / FIU Hospitality Review Journal / FIU Digital Commons, 2007)
Within the main elements of economic sustainability, socio-cultural sustainability, and environmental sustainability, the criteria of 'carrying capacity’ have ben emphasized through residents’ perception analysis to explore practical methods towards the application and implementation of such criteria. As data analysis revealed, the main tourist resources in the case of North Cyprus –the coast and the beach- have a certain capacity to sustain the impact and pressure of tourism. Despite the significance of the indigenous environment and with respect to the residents’ perception of optimum carrying capacity levels, this issue has not been given a due consideration. This has resulted in a process of coastal development which bypasses any measure ore application of a standard to harmonize the degree of physical development and the capacity of the beach. The main objective of this paper is to establish the concept of ‘carrying capacity’ as the means to achieve the reconciliation of environmental impacts with tourism development. The study concludes that, if carrying capacity measurement and its implementation are not incorporated into the planning decision as a clear policy, there will be grave negative consequences for those resources attracting visitors.
Keywords: Coastal Areas; North Cyprus; Tourism; North Cyprus